2016
DOI: 10.1016/j.rbmo.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Failure mode and effects analysis of witnessing protocols for ensuring traceability during PGD/PGS cycles

Abstract: Preimplantation genetic diagnosis and aneuploidy testing (PGD/PGS) use is constantly growing in IVF, and embryo/biopsy traceability during the additional laboratory procedures needed is pivotal. An electronic witnessing system (EWS), which showed a significant value in decreasing mismatch occurrence and increasing detection possibilities during standard care IVF, still does not guarantee the same level of efficiency during PGD/PGS cycles. Specifically, EWS cannot follow single embryos throughout the procedure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…There is not enough openness about the discussion of unwanted events, thus limiting our ability to learn from each other's mistakes. In fact, the use of tools for risk analysis in IVF is poorly documented and focuses on proactive tool applications whose versatility is well acknowledged [ 5 , 13 , 27 , 28 ]. To the best of our knowledge, this study showed for the first time the feasibility of a reactive tool for risk analysis of IVF processes, as it uncovers those nonadverse events that may potentially account for the final safety of care given.…”
Section: Resultsmentioning
confidence: 99%
“…There is not enough openness about the discussion of unwanted events, thus limiting our ability to learn from each other's mistakes. In fact, the use of tools for risk analysis in IVF is poorly documented and focuses on proactive tool applications whose versatility is well acknowledged [ 5 , 13 , 27 , 28 ]. To the best of our knowledge, this study showed for the first time the feasibility of a reactive tool for risk analysis of IVF processes, as it uncovers those nonadverse events that may potentially account for the final safety of care given.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, a partial loss of reproductive cells due to an incorrect management of biopsies could negatively impact reproductive chances of TESE patients. From this perspective, human witnessing was also considered essential to reduce some risks like incomplete crosscheck, involuntary automaticity and control omission (Cimadomo et al, ; de los Santos & Ruiz, ; Rienzi et al, , ; Toft & Mascie‐Taylor, ). To minimise these dangers, the FMEA team clearly defined essential the timing of witnessing (during and at the end of the procedure).…”
Section: Discussionmentioning
confidence: 99%
“…Usefulness of a quality system in reproduction [24] A novel embryo identification system by direct tagging of mouse embryos using silicon-based barcodes [25] Direct embryo tagging and identification system by attachment of biofunctionalized polysilicon barcodes to the zona pellucida of mouse embryos [26] Barcode tagging of human oocytes and embryos to prevent mix-ups in assisted reproduction technologies [27] Traceability of human sperm samples by direct tagging with polysilicon microbarcodes [28] Failure mode and effects analysis of witnessing protocols for ensuring traceability during IVF [29] Revised guidelines for good practices in IVF laboratories [30] Application of failure mode and effect analysis in an assisted reproduction technology laboratory [31] Failure mode an affects analysis of witnessing protocols of ensuring traceability during PGD/PGS cycles [32] Electronic witness system in IVF-patients perspective [33] Quality management in the IVF laboratory: Witnessing [34] Comprehensive protocol of traceability during IVF: The result of a multicentre failure mode and effect analysis [35] Different barcodes codification for embryo microlabeling [36] Development of a security system for assisted reproductive technology (ART) [37] Measuring human error in the IVF laboratory using an electronic witnessing system [38]…”
Section: Detection Selection Of Primary Studies and Data Extractionmentioning
confidence: 99%